2018
DOI: 10.1038/s41598-018-29371-0
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of TLR5 of different vertebrate species and diversification in intestinal pathogen recognition

Abstract: Toll-like receptor 5 (TLR5) is activated by bacterial flagellins and plays a crucial role in the first-line defence against pathogenic bacteria and in immune homeostasis, and is highly conserved in vertebrate species. However, little comparative information is available on TLR5 functionality. In this study, we compared TLR5 activation using full-length and chimeric TLR5 of various vertebrate species (human, chicken, mouse, pig, cattle). Chimeric TLR5 receptors, consisting of human transmembrane and intracellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 69 publications
4
8
0
Order By: Relevance
“…Several proinflammatory cytokines, including TNF-α, IL-1β, IL-6, KC, and IL-12 were induced in response to the purified FliC in a manner consistent with previous literature (Wyant et al, 1999; Eaves-Pyles et al, 2001; Hayashi et al, 2001; Moors et al, 2001; Kinnebrew et al, 2012). We also observed significant responses to lower doses of FliC (e.g., 0.05 μg), a finding consistent with prior studies that have reported activation of innate immune responses, including NF-κβ, TLR5, and host antimicrobial peptides following exposure to this level of FliC (Smith et al, 2003; Faber et al, 2018; Mowbray et al, 2018). We note that our use of a fliC mutant in these assays reflects a crucial control to conclude that the proinflammatory responses induced by FliC are not an artifact secondary to LPS contamination, which is an important consideration in studies of this type (Eaves-Pyles et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Several proinflammatory cytokines, including TNF-α, IL-1β, IL-6, KC, and IL-12 were induced in response to the purified FliC in a manner consistent with previous literature (Wyant et al, 1999; Eaves-Pyles et al, 2001; Hayashi et al, 2001; Moors et al, 2001; Kinnebrew et al, 2012). We also observed significant responses to lower doses of FliC (e.g., 0.05 μg), a finding consistent with prior studies that have reported activation of innate immune responses, including NF-κβ, TLR5, and host antimicrobial peptides following exposure to this level of FliC (Smith et al, 2003; Faber et al, 2018; Mowbray et al, 2018). We note that our use of a fliC mutant in these assays reflects a crucial control to conclude that the proinflammatory responses induced by FliC are not an artifact secondary to LPS contamination, which is an important consideration in studies of this type (Eaves-Pyles et al, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…22 This was not examined any further as part of this investigation. However, similar data regarding poTLR5 expression in HEK cells were published recently, 32 indicating that poTLR5 is non-responsive in HEK cells, despite the fact that the main adaptor, MyD88, shares a 94% homology between human and porcine MyD88 (Yamakawa and Werling, unpublished data).…”
Section: Discussionsupporting
confidence: 70%
“…To quantitate luciferase in NF-κB reporter cells, the Steady-Glo Luciferase Assay System (Promega) was used. Briefly, the lysis buffer-substrate mixture of the system was added to each well and the lysis was allowed to proceed as recommended by the manufacturer’s instructions [see also ( 54 )]. Lysed cells were analyzed for photon counts within 10 min after the lysis using a Clariostar multi-well reader (BMG Labtech) in luminescence mode (acquisition of photons for 10 s, no filter); output is quantitated as counts per second.…”
Section: Methodsmentioning
confidence: 99%